Estudo de viabilidade técnica na utilização de óleo vegetal como agente isolante e refrigerante em transformadores de distribuição - Ferreira, Paulo Roberto Nunes (Universidade Federal do Tocantins, 2019)
The understanding of the behavior of the insulating liquids when applied to distribution transformers overcame previously insurmountable obstacles due to the incipient technological evolution of that moment. Nowadays, with the application of modern techniques of chemical additives, and mainly by the improvement of the kinematic viscosity presented by the OVI, it has become competitive as a refrigerant and insulating substitute when compared to the IMO. In this context, this work sought to parallel the applications of OVI and IMO and their implications on the internal parts of the transformer, especially in relation to Kraft paper and metallic components, such as windings and core, in order to comparatively evaluate the advantages and disadvantages of the application of both regarding physical, chemical and electrical parameters. It has been shown that OVI, because of its OMI-like and sometimes superior characteristics, has surpassed and established itself as an ideal substitute for adding ecological and environmental characteristics superior to IMO. It has been found that OVI has an additional advantage over the flash point (high flash point), which mitigates the possibility of fire and explosions arising from high operating temperatures of the transformation equipment. In this study, modified soybean oil was used as substrate to be used as insulating fluid and refrigerant manufactured by Cooper Power system FR3, ENVIROTEMP³. Initially the physical, chemical and electrical properties of a regenerated mineral oil were analyzed and the characteristics of the three-phase transformer 13.8 kV and 15 KVA were previously known. The methodology used is the chemical, physical and electrical characterization of the soybean based vegetable oil, as well as the acidity index and kinematic viscosity in the external laboratory and the dielectric stiffness test in the field, after insertion of the OVI in this same transformer.